Trends in suicide attempts at an emergency department - Alves,Verônica M. (2017)
Objective: To characterize the profile of suicide attempts treated at an emergency department in the municipality of Arapiraca, state of Alagoas, Brazil, from 2009 to 2012. Methods: We analyzed all emergency department records containing a diagnosis of suicide attempt. Data were evaluated using Student’s t test and Pearson’s chi-square test. Significance was accepted at p<0.05. Results: We identified 2,142 cases. Suicide attempts were more frequent among women and young adults, but deaths were more frequent among men. Suicide attempts were most frequent among patients aged 10 to 39 years (81.1%). Drug intoxication (65.0%) and non-drug poisoning (16.2%) were significantly more prevalent than other methods of suicide. The month of April (10.6%) accounted for the greatest number of cases, and July had the smallest number (5.5%). Suicide attempts were most prevalent in spring (28.3%), on Sundays (18.4%) and Saturdays (16.8%), and from 12:00 p.m. to 5:59 p.m. Conclusion: Suicide prevention measures should focus on young women. Further research into the care provided to suicide attempters and better monitoring of the sale and use of medicines and poisons could be useful.